1997
DOI: 10.1097/00005373-199712000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Whole Blood Tumor Necrosis Factor Production upon Endotoxin Stimulation after Severe Blunt Trauma

Abstract: Major trauma leads to the appearance of a circulating inhibitory activity for TNF synthesis that may potentially contribute to an anti-inflammatory response in patients with multiple trauma. The elucidation of its structural and functional properties may contribute to the understanding of the pathogenesis of severely injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
30
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…Endotoxin tolerance has been described in bacterial LPS-pretreated macrophages as the impaired release of proinflammatory cytokines on a subsequent challenge with LPS (22). In accordance with previous findings, we demonstrated that induction of endotoxin tolerance reduced the LPS-induced expression and release of the proinflammatory cytokine IL-1␤.…”
Section: Discussionsupporting
confidence: 92%
“…Endotoxin tolerance has been described in bacterial LPS-pretreated macrophages as the impaired release of proinflammatory cytokines on a subsequent challenge with LPS (22). In accordance with previous findings, we demonstrated that induction of endotoxin tolerance reduced the LPS-induced expression and release of the proinflammatory cytokine IL-1␤.…”
Section: Discussionsupporting
confidence: 92%
“…These defects are illustrated by reports that stimulation of whole blood obtained from septic patients does not result in proinflammatory cytokine production (14,15,22). Several reports have also documented suppression of macrophage function following cecal ligation and puncture (4,47).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that LPS-stimulated blood cytokine production is generally down-regulated after trauma (2,8,13,14,23). However, in previous studies which presented individual alterations after surgical trauma, a remarkable proportion of patients showed enhanced cytokine responses upon LPS stimulation (13,23).…”
mentioning
confidence: 98%
“…Infection, severe injuries, and major surgical trauma are known to affect cellular immune functions, which are regarded to be responsible for increased susceptibility to secondary complications, e.g., sepsis and multiple-system organ failure (8,14,19). Similar to measurements of monocytic HLA-DR expression, detection of ex vivo lipopolysaccharide (LPS)-stimulated blood cytokine responses has been widely used as an indicator of compromised host defense mechanisms following accidental or surgical trauma (1,2,3,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation